Increasing blood donation in Egypt - Shafei, Azza Akram (AUC Knowledge Fountain, 2013)
Blood donation is becoming a critical national demand of emergency especially after Egypt’s revolution on the 25th of January 2011, and should be a high priority for the Ministry of Health (MOH) officials in order to save patients in need. This thesis investigated current barriers and possible incentives that would motivate more citizens to donate their blood. It explored factors that influence educated Egyptians’ decisions to donate blood, such as guidelines set before donating, efficiency of donation centers’ personnel, awareness regarding health gains, and the opportunity to rescue others. As a result of a qualitative and quantitative research, recommendations were formulated that could guide the MOH such as adjusting policies, equipping blood donation centers more appropriately, and promoting campaigns to increase willingness to donate blood in Egypt. Results in brief showed that face-to-face communication proved to be the most successful publicity measure. In addition, when doing campaigns, the government and the ministry have to be transparent regarding the phases of blood donation process and should take care to approach people coming from different social and educational backgrounds through proper methods. The most common barriers were fear of: pain, lack of hygiene and fear of getting infected, but lack of donations is also because of recent governmental policies: forbidding paid blood donation and monopolizing blood donation. The survey findings to an extent supported a conclusion that confidence in personal physical capabilities as well as trust in the blood donation staff efficiency and the process as a whole would lead to a rise in the willingness to donate blood.